Tax Intensification and Extensification in Enhancing Local Tax Revenue: Evidence from the Regional Revenue Agency of Berau Regency - Roni Sander Saranga; Hendrik Gunadi (Master of Management Study Program, Universitas Kristen Indonesia Paulus, 2026)
Local tax revenue represents a crucial component in strengthening regional fiscal capacity and supporting sustainable regional development. Efforts to optimize tax revenue can be implemented through tax intensification and tax extensification strategies conducted by local governments. This study aims to examine the role of tax intensification and tax extensification in improving local tax revenue at the Regional Revenue Agency of Berau Regency. A quantitative approach was employed using a survey method involving 40 employees of the Regional Revenue Agency who are directly involved in local tax management. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of IBM SPSS version 31.00. The results indicate that tax intensification and tax extensification demonstrate positive and significant relationships with local tax revenue. Partially, tax intensification shows a t-value of 3.991 and tax extensification a t-value of 4.192, both exceeding the t-table value of 2.026 with significance levels below 0.05. Simultaneously, the two variables also demonstrate statistical significance with an F-value of 23.143, which is higher than the F-table value of 4.11. These findings highlight that strengthening tax administration, improving taxpayer compliance, and expanding the tax base contribute to the enhancement of local tax revenue.